Hubungan Kecemasan dan Dukungan Sosial Dengan Bonding Attachment Pada Ibu Postpartum Saat Pandemi Covid-19 Di Wilayah Kerja Puskesmas Bekasi Jaya - Anisa Nurhazyima (2021)
The Covid-19 pandemic has made postpartum mothers experience anxiety. Social support is important as a coping mechanism for postpartum mothers who experience anxiety. Social support will affect mothers' psychological condition and bonding attachment. The purpose of this study is to determine the correlation between anxiety and social support with bonding attachment in postpartum mothers during the Covid-19 pandemic in the working areas of puskesmas Bekasi Jaya. The research design of this uses descriptive analytic with a cross sectional approach. The sampling technique of this research uses total sampling with a total of 50 respondents. The research instruments used were Zung Self Rating Anxiety Sacle (ZSAS), Multidimensional Sacle of Perceived Social Support (MSPSS), and Postpartum Bonding Quesionnair (PBQ). The results of the analysis using the chi square test showed that there was a relationship between anxiety and bonding attachment (p value 0.001), and there was no a relationship between social support with bonding attachment (p value 0.075). The social environment of the postpartum mothers is expected to be able to provide support and motivation for postpartum mothers to assist coping mechanisms in overcoming psychological disorders and bonding attachments.